Hubungan Self Control Dengan Prokrastinasi Akademik Mahasiswa Jurusan Ilmu Pendidikan 2016 - Noven Azalia; Muswardi Rosra; Redi Eka Andriyanto (ALIBKIN (Jurnal Bimbingan Konseling), 2019)
The problem in this research was the high level of student academic procrastination. This study aims to determine the correlation between self-control and academic procrastination for the students of the science education major of Education and Teacher TrainingFaculty (FKIP) ata batch of  2016. The research method was quantitative. The research population was 255 students and the sample was 146 students taken by a voluntary sampling technique. The data collection technique used a standard scale of self-control and the standard scale of academic procrastination. The data analysis technique used the Product Moment correlation. The results showed that there was a strong negative significant correlation between self-control and academic procrastination on the students of the science education major of Education and Teacher Training Faculty (FKIP) at a batch of 2016.Permasalahan dalam penelitian ini adalah tingkat prokrastinasi akademik mahasiswa yang tergolong tinggi. Penelitian ini bertujuan untuk mengetahui hubungan antara self control dengan prokrastinasi akademik pada mahasiswa jurusan ilmu pendidikan fakultas keguruan dan ilmu pendidikan angkatan 2016. Metode penelitian bersifat kuantitatif. Populasi penelitian ini sebanyak 255 mahasiswa dan sampel penelitian ini berjumlah 146 mahasiswa diambil dengan teknik voluntary sampling. Teknik pengumpulan data menggunakan skala baku self control dan skala baku prokrastinasi akademik. Teknik analisis data menggunakan korelasi Product Moment. Hasil penelitian menunjukkan bahwa terdapat hubungan negatif signifikan yang kuat antara self control dan prokrastinasi akademik, pada  pada mahasiswa jurusan ilmu pendidikan fakultas keguruan dan ilmu pendidikan angkatan 2016.Kata kunci: bimbingan dan konseling, prokrastinasi akademik, self control